2016
DOI: 10.1038/modpathol.2015.129
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant loss of SMARCA2 and SMARCA4 expression in small cell carcinoma of the ovary, hypercalcemic type

Abstract: Small cell carcinoma of the ovary, hypercalcemic type is an aggressive tumor generally affecting young women with limited treatment options. Mutations in SMARCA4, a catalytic subunit of the SWI/SNF chromatin remodeling complex, have recently been identified in nearly all small cell carcinoma of the ovary, hypercalcemic type cases and represent a signature molecular feature for this disease. Additional biological dependencies associated with small cell carcinoma of the ovary, hypercalcemic type have not been id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
58
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 22 publications
1
58
0
Order By: Relevance
“…Albeit rare, small cell carcinoma of hypercalcemic type should also be considered in the differential diagnosis of an ovarian small round blue cell tumor in a young patient. While small cell carcinoma of hypercalcemic type consists of sheets of small round blue cells that may stain for neuroendocrine markers similar to PNET, there are usually at least focal follicle formation and less frequently minor foci of mucinous epithelium; variable nuclear WT1, EMA and cytokeratin expression; and loss of BRG1 and BRM expression that are distinctive from PNET (6668). …”
Section: Discussionmentioning
confidence: 99%
“…Albeit rare, small cell carcinoma of hypercalcemic type should also be considered in the differential diagnosis of an ovarian small round blue cell tumor in a young patient. While small cell carcinoma of hypercalcemic type consists of sheets of small round blue cells that may stain for neuroendocrine markers similar to PNET, there are usually at least focal follicle formation and less frequently minor foci of mucinous epithelium; variable nuclear WT1, EMA and cytokeratin expression; and loss of BRG1 and BRM expression that are distinctive from PNET (6668). …”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, these lines do not have any described coding mutations in SMARCA2, suggesting that the mechanism of SMARCA2 inactivation is possibly through epigenetic silencing, as has been described previously to occur in SCCOHT and other indications (23,24). As dual loss of SMARCA2 and SMARCA4 has been recently demonstrated to be a defining characteristic of SCCOHT within ovarian cancer (23,24), these observations highly suggest that TOV112D, OVK18, and COV434 cell lines are derived from SCCOHT tumors that were misdiagnosed as a different ovarian cancer subtype. Interestingly, granulosa cell tumors, from which COV434 was derived, are categorized as a form of ovarian cancer that is known to mimic SCCOHT morphologically (36).…”
Section: Dual Loss Of Smarca2 and Smarca4 Protein Identifies Three MImentioning
confidence: 91%
“…Interestingly, in a rare type of ovarian cancer, small-cell carcinoma of the ovary, hypercalcemic type (SCCOHT), SMARCA4 and SMARCA2 have been found to be coinactivated. SMARCA4 activity is lost via genomic mutations, whereas SMARCA2 mRNA is lost in the absence of any coding mutations (19)(20)(21)(22)(23)(24). Increasing evidence now suggests that the dual loss of SMARCA2 and SMARCA4 is a molecular signature and defining feature of SCCOHT.…”
Section: Introductionmentioning
confidence: 99%
“…The results of the current and prior studies indicate that loss of SMARCA4 expression is a highly sensitive and specific immunohistochemical marker of SCCOHT. Of the ~3600 cases of non‐SCCOHT ovarian, uterine and non‐gynaecological tumours studied to date (Tables and ), only a few cases have been noted to lack expression of SMARCA4: one case of uterine endometrioid carcinoma (1/360; <1%); 16 cases of endometrial dedifferentiated/undifferentiated carcinoma (16/59; 27%); four cases of uterine endometrial stromal sarcoma (4/53; 7.5%); one melanoma metastatic to ovary of the 47 primary or metastatic melanomas tested (1/47; 2.1%); and 17 ovarian clear‐cell carcinomas (17/447; 3.8%), although these tumours are not typically considered in the differential diagnosis of SCCOHT …”
Section: Discussionmentioning
confidence: 99%
“…In the initial articles describing the molecular alterations and in subsequent follow‐up studies, loss of SMARCA4, or rarely SMARCB1, expression has been shown to be highly sensitive for SCCOHT, being demonstrated in 109 of 114 (96%, including 106 SMARCA4‐deficient and three SMARCB1‐deficient) cases (Table ) (Figure ) . To date, ~3600 cases of ovarian (epithelial, sex cord–stromal, and germ‐cell), uterine (epithelial and stromal) and non‐gynaecological tumours have been studied (Tables and ) for SMARCA4 expression, with the vast majority of cases showing retained expression . This suggests that SMARCA4 is a highly sensitive and specific marker for SCCOHT.…”
Section: Introductionmentioning
confidence: 99%